Pelatihan Perancangan Asesmen Non-Tes untuk Meningkatkan Kapasitas Calon Guru BK dalam Analisis Kebutuhan Siswa - Salsabila Nasution; Nurfaidah Ardis; Inayah Ridhayanti Qarimah; Abid Raisardhi Abdullah; Siska Putri Ayu (Universitas PGRI Palembang, 2026)
Assessment is an important aspect of guidance and counseling in schools. This service aims to improve the capacity of prospective guidance and counseling teachers in designing non-test assessments and analyzing student needs through workshop-based training. The training was attended by 29 guidance and counseling students and was held on March 4, 2026. The methods used included lectures, group discussions, hands-on practice, and presentation of results. Before and after the training, pre-tests and post-tests were conducted to measure participants' understanding. The pre-test results showed that some participants had a low understanding of non-test assessments, while after the training, all participants showed significant improvement and were in the high category. These findings indicate that training that combines theory with hands-on practice is effective in bridging the gap between theoretical knowledge and practical skills of prospective BK teachers. This community service has a positive impact on prospective BK teachers in designing non-test assessment instruments that are relevant to student needs, as well as improving their ability to plan data-based BK programs.